Energy Saving Electrochromic Polymer Windows with a Highly Transparent Charge‐Balancing Layer. (14th July 2017) - Kim, Younghoon; Shin, Haijin; Han, Minsu; Seo, Seogjae; Lee, Woojae; Na, Jongbeom; Park, Chihyun; Kim, Eunkyoung
Abstract : Highly transparent TiO2 nanoparticles are explored as a non‐electrochromic (non‐EC) charge‐balancing layer for a high color contrast, bistable electrochromic window (ECW). The TiO2 nanoparticle (TNP) layer increases the potential at the EC polymer electrode, thereby lowering the working voltage of the ECW. This leads to lower the power consumption of ECWs without loss in the high color contrast (Δ T > 72%) and to remarkably improve the cyclability (Δ T change <1% over 3000 cycles), mainly due to the low overvoltage (<0.1 V) on the electrochromic polymer layer. Furthermore, the ECWs including the non‐EC TNP layer show long‐term bistability (>2.7 h, 40% increase) and UV stability (Δ T change <1%) to provide a low‐power automatic ECW. This finding shows that the charge balanced ECP window has the potential to be used for an energy saving ECW with low‐power consumption and will be widely applied in various ECWs as well as electrochemical devices with multiple functions. Abstract : Reducing the overvoltage on the polymeric electrochromic layer, along with TiO2 nanoparticles as a non‐electrochromic charge‐balancing layer, an electrochromic window shows high color contrast, low‐power consumption, fast switching, high coloration efficiency with long cyclability, and durability under ultraviolet irradiation. This methodology can be extended to other types of electrochromic windows as well as various types of electrochemical devices to find maximum function.